An analytical expression for the K shell ionization cross section of some heavy atomic elements by electron impact - Salim Al-Shamma; Muzahim Azawi; Lubna Ismail (College of Education for Pure Sciences, 1970)
Abstract: An analytical expression is proposed to describe the k shell ionization cross section by electron impact for some heavy atomic elements (Ho, Yb, W, Au, Pb, and U) had been presented. This study is based on the analysis of the calculated cross section using Sbell formalism. The proposed analytical expression had been found to be fitted very well with the shape of the calculated data for all atomic elements with an acceptable agreement in the values of the calculated cross section.